Implant-related sepsis in lower limb fractures following gunshot injuries in the civilian population: A systematic review. Issue 2 (February 2019) - Graham, Simon Matthew; Wijesekera, Maheshi P.; Laubscher, Maritz; Maqungo, Sithombo; Held, Michael; Ferreira, Nando; Harrison, William J.
Abstract: Introduction: The management of long bone lower limb fractures secondary to gunshot wounds (GSWs) in the civilian setting are complex and there is currently no consensus regarding the optimal approach to managing such fractures. This study aims to address the relationship of implant related sepsis in fractures secondary to GSWs. Methods: A systematic review of the literature was performed on both Pubmed and Scopus databases that look at fractures caused by GSWs in the lower limb. A total of 14 studies met the inclusion criteria set in this study. Results: Current literature suggests that low and high velocity injuries managed with internal fixation, such as intramedullary nails, may carry a low risk of superficial and deep infection, with no obvious risk of osteomyelitis. However, infection was poorly defined across all studies and no study used a validated scoring system for infection making it difficult to draw any valid conclusion on the rate of infection following internal fixation of lower limb fractures following both high and low velocity GSWs. Conclusion: There is no clear evidence to confirm or refute that internal fixation is the ideal method of management in these complex injuries and guidance is needed due to the high and increasing proportion of patients presenting with these complex injuries worldwide.